The Function and Purpose of Education in the Qur'an - Azmi Arroisiy; Ahmad Mohammad Tijani (Penerbit Hellow Pustaka, 2025)
Islam exists not merely as a concept of belief, but as a primary source of reference for life, providing lessons for every aspect of human life. In this context, the concept of Islamic education becomes an ideal educational alternative that positions humans as educators in educating others. Therefore, education cannot be separated from its function and purpose. In Islam, the Quran plays a crucial role and serves as a reference for the lives of Muslims, including education. In this paper, the author will explain the function and purpose of education in the Quran. In his analysis, he will not forget to compare the opinions of various Muslim scholars to enrich the study of the function and purpose of Islamic education. Likewise, the views of various modern educational figures are also compared in this study.